2021
DOI: 10.56499/jppres21.1108_9.6.921
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic fraction concentrate of Phoenix dactylifera L. seeds: A promising antioxidant and glucose regulator

Abstract: Context: The beneficial effects of natural polyphenolic compounds are increasingly emerging as powerful antioxidants and digestive boosters. Phoenix dactylifera seeds are recently identified as a healthy functional food with rich amounts of phenolic compounds. Aims: To analyzing the phenolic profile obtained from Moroccan variety of date seeds and evaluating the inhibitory capacity against digestive enzymes and the antioxidant potential of phenolic fraction concentrate (PFC) of date seeds as a promising antih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…As a result, previous research discovered that some phenolic acids such as caffeic and gallic acids protected rodents against chronic stressinduced disturbances (41,42). We suggest that the observed effects of PFCs in diabetic rats exposed to CMS might be linked to their significant amounts of phenolic acids, especially caffeic acid (25). In this context, interest in phenolic acid compounds has increased, mainly due to their anti-inflammatory, antioxidant, and antidiabetic properties against numerous chronic diseases.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…As a result, previous research discovered that some phenolic acids such as caffeic and gallic acids protected rodents against chronic stressinduced disturbances (41,42). We suggest that the observed effects of PFCs in diabetic rats exposed to CMS might be linked to their significant amounts of phenolic acids, especially caffeic acid (25). In this context, interest in phenolic acid compounds has increased, mainly due to their anti-inflammatory, antioxidant, and antidiabetic properties against numerous chronic diseases.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study has shown that monotherapy treatment with insulin did not protect patients against cognitive dysfunction and emotional disorders, including stress-related to T1DM (40). The exhibited PFCs effects might be explained by their significant antioxidant and antidiabetic effects (25). As a result, previous research discovered that some phenolic acids such as caffeic and gallic acids protected rodents against chronic stressinduced disturbances (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations